What Can Queer Theory Do for Intersex? - Morland, Iain (GLQ: A Journal of Lesbian and Gay Studies, 2009)
In this essay I explore how queer theory might account for postsurgical intersex bodies of diminished genital tactility. In other words, I evaluate whether a critique of surgery’s effects is possible from a queer theoretical perspective on the body. I contend that for this purpose queer theory must do more than focus on bodily sensations such as pleasure, shame, and touching. The essay makes four key claims: first, that the desensitized postsurgical body cannot be accounted for by a queer discourse in which sexual pleasure is a form of hedonistic activism; second, that a queer discourse of shame enables a degree of critical engagement with the surgical creation of atypically sensate bodies; third, that pleasure and shame are both queer sensations, and queer theory’s assumption of a sensorial basis to cultural critique, which is exemplified by the queer touch, flounders when confronted with the desensitized intersex body; fourth, that if queer theory is figured as a kind of reaching—but not necessarily touching—then it can be of greater use in accounting for the problematic yet ambivalent effects of intersex surgery.
Keywords: LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; premier cycle; queer; ressource en ligne; thématiques; études culturelles; études littéraires

Les subalternes peuvent-elles parler? - Spivak, Gayatri Chakravorty..; Vidal, Jérôme.. (Éd. Amsterdam, 2009)
Dans le cadre d'un dialogue critique avec Michel Foucault, Gilles Deleuze et la tradition marxiste, G.C. Spivak articule le concept de subalterne (à ne pas confondre avec les notions de minoritaire ou d'opprimé) et s'interroge sur les femmes subalternes du tiers-monde, l'unification des subalternes au sein d'une communauté.
Keywords: approches et analyses; arts; care; com5170; corps; cours; discipline; féminisme décolonial; har4600; histoire et politique; incontournable; oui; premier cycle; thématiques; études littéraires; études postcoloniales

Cyborgs et corps piratés dans la littérature de science-fiction - Bréan, Simon (Critique, 2008)
« 50 % homme, 50 % machine, 100 % flic ! » : Robocop est un policier torturé par des criminels et qui ne doit la vie qu’à des implants cybernétiques. Son exosquelette électronique en fait le meilleur policier des États-Unis : invulnérable, mais aussi précis, intègre, infaillible. Moins humain pourtant que le slogan ne pourrait le faire croire, Robocop se heurte à une directive secrète implantée dans son cerveau informatisé et l’empêchant d’arrêter un dirigeant corrompu de la société qui en a fait un cyborg. Privé de son libre-arbitre, l’homme cybernétique paie d’une partie de son humanité ses améliorations physiques. Robocop incarne les fantasmes ambivalents suscités par la cybernétique, à la fois promesse d’un dépassement de l’humanité à l’aide des machines et hantise d’un piratage du corps humain par la technologie. C’est à travers ce genre d’images frappantes que la science-fiction évoque de manière ludique les conséquences possibles de recherches scientifiques. Toutefois, le cyborg est moins une figure élaborée à partir de la cybernétique elle-même que l’incarnation d’un désir diffus, celui d’une participation de plus en plus intime de l’être humain aux progrès technologiques. La cybernétique comme discipline scientifique peut être définie comme la science des systèmes, dans la mesure où elle s’intéresse à la façon dont les parties d’un ensemble interagissent entre elles. L’analyse cybernétique s’applique aussi bien au corps humain qu’à une machine, même s’il n’existe entre les deux qu’un rapport d’homologie…
Keywords: approches et analyses; arts; cibernétique; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences; technologie; thématiques; études littéraires

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

The master’s tools will never dismantle the master’s house - Lorde, Audre (Sister outsider: essays and speeches, 2007)
Première édition: 1984
Keywords: afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; fem3600; féminisme afroaméricain; histoire et politique; lesbianisme; militance; premier cycle; régions géographiques; thématiques; émotions; états-unis; études littéraires

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Body art and performance: the body as language - Vergine, Lea; Vergine, Lea (Skira, 2007)
When The Body as Language ("Body-art" and Performance) appeared in 1974, it was immediately a huge publishing hit, reviewed by some of the most influential art historians and writers (Giulio C. Argan, Edoardo Sanguineti, Max Kozloff, Lucy Lippard, François Pluchart, Peter Gorsen, Evelyn Weiss and many others). A direct testimony of the birth and development of one of the most controversial art trends, Lea Vergine's book avails of a series of texts by the artists themselves, whom the author had asked to contribute with a statement about the illustrations of their work. Featuring a thorough documentation of original photographs and film photograms, videotapes, happenings, actions and performances, the book analyses the evolution of this phenomenon through the works of sixty artists, including Gina Pane, Gilbert & George, Urs Lüthi and Katharina Sieverding, Rebecca Horn, Trisha Brown, Günter Brus and many others who have worked with and on the body. In an absolutely unusual publishing event, nearly thirty years after the first edition, the text–by now a classic–is republished with all the original photographic material. The volume is enhanced and brought up-to-date by an afterword by Lea Vergine, who observes the changes of Body Art throughout the nineties: Orlan, Stelarc, Ron Athey, Franko B., Yasumasa Morimura, Jana Sterbak, Matthew Barney are "virtuosos of disorder and hungry for afflictions of any and every kind, mystics–like persons who display the subjection of their bodies to cruel and invasive devices, or who revel in virtual fantasies of such self-inflicted pains–destroy themselves in order newly to find themselves. . . . They finally pay a visit to the world of the saints and victims, exploring and prolonging its seductions.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; performance; premier cycle; thématiques

Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
OCLC: ocm61879732
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."–Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Travestissement féminin et liberté(s) - Leduc, Guyonne (L'Harmattan, 2006)
Ce livre nous invite à découvrir les nombreuses facettes du travestissement féminin dans la culture occidentale des XVIè-XXè siècles. Pourquoi se travestir ? Par amour, par patriotisme, pour fuir des violences domestiques, pour vivre une aventure... Les motifs sont multiples. Travestissement, et non femmes travesties : l'ouvrage s'intéresse avant tout au formidable révélateur social, culturel et esthétique qu'est le travestissement. Il met à nu le mécanisme de la construction des genres ; il dévoile l'ordre sexuel qu'il défie.
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; genre; har4600; histoire et politique; identités LGBTQIA2+; outils; premier cycle; rapports sociaux de sexe; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; travestissement; études littéraires

Le modelage du corps et de l'esprit féminins dans Histoire d'Omaya (1985) de Nancy Huston : une critique des représentations de genre - Patenaude, Judith (Université du Québec à Montréal, 2006)
Dans les sociétés occidentales, malgré le progrès significatif des droits des femmes, les représentations culturelles demeurent, encore aujourd'hui, très souvent misogynes. Cette phallocratie symbolique est particulièrement apparente dans la pornographie et dans la littérature érotique, mais elle se manifeste également dans les médias de masse, où son danger potentiel est décuplé par la multiplication exponentielle des moyens de diffusion, caractéristique de l'époque postmoderne. Nancy Huston fait partie de ces auteures féministes qui, tant par la théorie que par la fiction, cherchent à mettre en évidence la violence de ces images ainsi que leurs conséquences dans la vie des femmes. Par le biais d'une parodie du roman pornographique Histoire d'O, de Pauline Réage, elle s'en prend à la soumission sexuelle des femmes et surtout, à la prégnance de cette représentation dans l'imaginaire collectif. Notre mémoire aborde la manifestation de cette critique dans son roman Histoire d'Omaya, qui, contrairement au roman de Réage, dépeint une femme qui refuse la violence qui lui est imposée. Une étude de l'image traditionnelle de la femme dans la pornographie et la littérature érotique est proposée et, à l'aide de théories féministes postmodernes sur la parodie, les différentes marques de la critique d'Histore d'O sont analysées. Parmi ces marques, l'omniprésence du regard masculin est davantage développée, puisque celui-ci représente un élément central du roman de Huston. Ce regard participe non seulement à la réification de la protagoniste mais constitue également un prélude au viol. Enfin, une analyse de la polyphonie constituante du roman est présentée, de manière à mieux comprendre l'aspect contestataire que revêt cette forme narrative erratique et hérétique. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : littérature érotique, pornographie, Pauline Réage, Nancy Huston, parodie, regard, réification, polyphonie, hystérie, postmodernisme, féminisme, genre.
Keywords: IREF; arts; corps; corps féminin; discipline; genre; identités LGBTQIA2+; littérature érotique; mémoires/thèses; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

Saphisme et décadence dans Paris fin-de-siècle - Albert, Nicole G. (La Martinière, 2005)
Figures emblématiques des années 1900, les saphistes sont associées aux premiers balbutiements d'un féminisme qui dérange et qui, par réaction, nourrit d'inépuisables fantasmes. Objets de scandale ou héroïnes, elles inspirent artistes et poètes. C'est l'ensemble de ces représentations ambiguës qui sont ici analysées.
Keywords: 1800-1899; approches et analyses; arts; corps; discipline; discours dominant; europe; france; lesbianisme; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; études littéraires

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Number: 1
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Le corps de l'artiste - Warr, Tracey; Jones, Amelia; Warr, Tracey; Jones, Amelia (Phaidon, 2005)
Au cours du XXe siècle, de nombreux artistes ont utilisé leur corps à la fois comme sujet et comme objet de leur oeuvre. Le corps est présenté dans tous les états possibles et l'artiste vit littéralement son art que ce soit dans le cadre de performances, ou dans l'intimité, avec la photographie et la vidéo. Ouvrage conçu par T. Warr.
Keywords: 1900-1999; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; thématiques

Caught in the act: an anthology of performance art by Canadian women - Mars, Tanya; Householder, Johanna; Mars, Tanya; Householder, Johanna (YYZ Books, 2004)
This indispensable anthology gives readers access to an important and under-recognized subject in recent Canadian art history. Edited by two seminal Canadian performance artists, this book focuses on the 70s and 80s; a time when women made a big and noisy impact. Full of sass and insight, this essential collection is part survey, part critical discourse, and part reference book, containing five critical essays, thirty-four artist's profiles, and an extensive bibliography.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; art contemporain; arts; canada; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques

X-elles: le sexe par les femmes - Millet, Catherine..; Leydier, Richard 19.... (Art Press, 2004)
"Adresses Internet p. 112-113."Contient : Editorial : un raz de marée, par Catherine Millet et Richard Leydier, p. 5-7. Chapitre 1 : Elles débarquent! : L'acte pour l'art, par Louis-José Lestocart, p. 10-14 ; Bandes de femmes, par Bernard Joubert, p. 15-21 ; Éros féminin surréel, par Victoria Combalía, p. 22-27 ; Ellen von Unwerth. Naughty Girls!, interview par Richard Leydier, p. 28-31 ; Organes et orgasmes. Sur quelques chanteuses sexy, par Stéphane Pencréac'h, Stéphane Ruiz et Richard Leydier, p. 32-36; Dans le train fantôme de Catherine Breillat, témoignages recueillis par Brigitte Ollier, p. 37-40 ; Clarisse Hahn. La sexualité dans le tissu de la vie, interview par Catherine Millet et Louis-José Lestocart, p. 41-44 ; Portfolio #1 : Aude du Pasquier-Grall, Sonia Koumskoff-Raissi, Nicole Tran Ba Vang, Ornela Vorpsi, Friedl Kubelka, Anne Dion., p. 45-50. Chapitre 2 : Un autre porno : Angela, Loulou et les autres ... Quand les femmes prennent la caméra, par Stéphane Ruiz, p. 52-60 ; Monika Treut. Female Misbehavior, par Thibaut de Ruyter, p. 61-65 ; Maria Beatty. De la surface à la profondeur, par Catherine Corringer, p. 66-70 ; Shu Lea Cheang. Un genre en soi, Interview par Louis-José Lestocart, p. 71-74 ; Il y a une vie après le X : Brigitte, Tabatha, Ilona et Traci, par Laurent Goumarre, p. 75-80 ; Ovidie, plus librement, interview par Laurent Goumarre, p. 81-84 ; Portfolio #2 : Kiki Seror, Virginie Boursette, Béatrice Cussol, Bettina Rheims, Pascale Lafay, Diana Michener, p. 85-90. Chapitre 3 : Autoportraits : Lamia Ziadé. "Je suis une vraie petite femme d'intérieur", interview par Brigitte Ollier, p. 92-96 ; Chloë des Lysses. Une femme en danger, interview par Richard Leydier, p. 97-101 ; Madeleine Berkhemer. Élastique, érotique, par Alix Rozès, p. 102-105 ; Elke Krystufek. Le miroir qui met à nu, interview par Joerg Bader, p. 106-109 ; La pornographie, to remember, par Judith Brouste, p. 110-111 ; Les femmes sur le Web, par Chloë des Lysses, p. 112-113.
Keywords: 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; europe; france; har4600; histoire de l'art; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques

Masculinities without men? female masculinity in twentieth-century fictions - Noble, Jean Bobby (UBC Press, 2004)
Les idées conventionnelles sur le genre et la sexualité dictent que les personnes nées avec un corps masculin possèdent naturellement à la fois une identité masculine et un droit à l'autorité. Des recherches récentes dans le domaine des études de genre exposent cependant les technologies politiques complexes qui construisent le genre comme une essence biologique supposée immuable avec des liens évidents avec la physicalité, l’identité et le pouvoir. Dans des masculinités sans hommes ? Jean Bobby Noble explore comment la construction du genre a été mise en crise au cours du XXe siècle, entraînant une rupture permanente du système sexe/genre, et comment la masculinité est devenue une catégorie instable, modifiée au fil du temps, de la région, de la classe sociale et de l'origine ethnique.
Keywords: 1900-1999; arts; cinéma; corps; discipline; genre; histoire et politique; identité sexuelle; identités LGBTQIA2+; littérature; médias; personnes lesbiennes; personnes trans*; périodes historiques; ressource en ligne; sexualité; thématiques; études littéraires

Gender, discourse, and desire in twentieth-century Brazilian women's literature - Pinto, Cristina Ferreira (Purdue University Press, 2004)
This study by Cristina Ferreira-Pinto explores the poetic and narrative strategies twentieth-century Brazilian women writers use to achieve new forms of representation of the female body, sexuality, and desire. Female writers discussed include: Gilka Machado, Lygia Fagundes Telles, Marcia Denser, and Marina Colasanti. While creating new forms, these writers are also deconstructing cultural myths of femininity and female behavior. In order to understand these myths, the book also presents new readings of some male-authored canonical novels by Jose de Alencar, Machado de Assis, Manuel Antonio de Almeida, and Aluisio Azevedo. The specific focus on female sexuality and desire acknowledges the intrinsic link between sexuality and an individual's sense of identity, and its importance for female identity, given the historical repression of women's bodies and the double standard of morality still pervasive in many Western cultures. In the discussion of the strategies Brazilian female poets and fiction writers employ, Ferreira-Pinto addresses some social and cultural issues that relate to a woman's sense of her own body and sexuality: the characterization of women based on racial features and class hierarchy; marriage; motherhood; the silencing of the lesbian subject; and aging. Ferreira-Pinto's analysis is informed by the works of various and diverse critics and theoreticians, among them Helene Cixous, Teresa De Lauretis, Adrienne Rich, Gloria Anzaldua, Georges Bataille, and Wilhelm Reich.
Keywords: amériques; arts; brésil; corps; discipline; histoire et politique; littérature; maternité; ressource en ligne; régions géographiques; sexualité; thématiques; violences; écriture des femmes*; études littéraires

The literature of lesbianism: A historical anthology from Ariosto to Stonewall - Castle, Terry (Columbia University Press, 2003)
Depuis la Renaissance, d’innombrables écrivains ont été aimantés par la notion d’amour entre femmes. Des poèmes d'amour de la Renaissance aux romans, pièces de théâtre et nouvelles du XXe siècle, La Littérature du Lesbianisme rassemble des centaines d'œuvres littéraires sur le thème de l'homosexualité féminine. Il ne s’agit pas d’une anthologie d’« écrivains lesbiennes ». Il ne s’agit pas non plus simplement d’un recueil unilatéral d’images « positives » ou « négatives » de l’expérience lesbienne. Terry Castle explore l'émergence et la transformation de « l'idée du lesbiennesme » : ses origines conceptuelles et la façon dont elle a été transmise, transformée et embellie collectivement au cours des cinq derniers siècles. Les auteurs masculins et féminins sont ici représentés et affichent une diversité d'attitudes étonnante et souvent imprévisible. Certains critiquent l’amour féminin entre personnes de même sexe ; certains en font l’éloge. Certains sont salaces ou satiriques ; d’autres sympathiques et confessionnels. Pourtant, ce qui ressort partout, c’est à quel point l’amour saphique a toujours été visible – en tant que thème littéraire – dans la littérature occidentale. Comme le démontre Castle, ce n’est pas un sujet tabou ou interdit que nous supposons parfois, mais il a en fait été une préoccupation centrale pour nombre de nos plus grands écrivains, passés et présents. Commençant par un extrait du poème épique comique de l'Arioste, Orlando Furioso,l'anthologie progresse chronologiquement à travers les cinq siècles suivants, présentant des sélections de Shakespeare, John Donne, Katherine Philips, Aphra Behn, Sor Juana Ines de la Cruz, Alexander Pope, le marquis de Sade, Samuel Taylor Coleridge, Charlotte Brontë, Emily Dickinson, Guy de Maupassant, Henry James, Willa Cather, Virginia Woolf, Ernest Hemingway, Nella Larsen, Colette et Graham Greene, entre autres. Il comprend également des œuvres anonymes, dont plusieurs publiées ici pour la première fois, ainsi que de nombreuses traductions d'écrivains de l'Antiquité, tels que Sappho, Ovide, Martial et Juvénal, dont la redécouverte au début de la Renaissance a contribué à façonner les représentations littéraires occidentales ultérieures de homosexualité féminine.
Keywords: approches et analyses; arts; corps; discipline; identités LGBTQIA2+; lesbianisme; outils; ouvrages de références; sexualité; thématiques; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Veil: veiling, representation, and contemporary art - Tawadros, Gilane; Bailey, David A. (MIT Press ; IVA, 2003)
No single item of clothing has had greater influence on Western images of Middle Eastern and North African women than the veil. The fascination of Western writers, artists, and photographers with the veil reflects the voyeuristic nature of our interest in what is strange and "other." Veil, which accompanies an exhibition organized by the Institute of International Visual Arts in London, explores the representation of the veil in contemporary visual arts. Providing a context for the commissioned essays are a number of classical historical texts crossing religions, cultures, genders, and ages–from Greek myths to articles published in the aftermath of September 11, 2001. Some of the contemporary artists and scholars write autobiographically about the meaning of the veil in their lives. Others take a more political approach, discussing, for example, how the events of September 11 changed the use and reception of veil imagery throughout the world. Still others take a historical approach, examining how nineteenth-century technological developments in travel and photography led to photographic depictions of both the veiled and unveiled body in relation to landscape. A number of essays look at the art historical precedents for the current interest in artwork addressing the veil, while others examine how codes of modesty and gender segregation have affected the making and viewing of films in postrevolutionary Iran. The essays are by Jananne Al-Ani, David A. Bailey, Alison Donnell, Ghazel, Salah Hassan, Reina Lewis, Hamid Naficy, Zineb Sedira, and Gilane Tawadros. The artists represented include Faisal Abdu'Allah, Kourosh Adim, Ghada Amer, Jananne Al-Ani, Farah Bajull, Samta Benyahia, Gaëtan de Clérambault, Marc Garanger, Shadafarin Ghadirian, Group AES, Emily Jacir, Ramesh Kalkur, Shirin Neshat, Harold Offeh, Gillo Pontecorvo, Zineb Sedira, Mitra Tabrizian, and Elin Strand.
Section: 187 p. : illustrations en noir et en coul. ; 22 cm
Keywords: afrique; afrique du nord; approches et analyses; arts; corps; cours; discipline; féminisme islamique; har4610; histoire de l'art; mode; moyen-orient; point de vue situé; premier cycle; régions géographiques; thématiques; vêtements

Lectures du genre - Boisclair, Isabelle (Les éditions du remue-ménage, 2002)
Qu’en est-il du masculin et du féminin dans la production littéraire contemporaine? Que permettent d’apprendre sur les textes du passé les hypothèses actuelles quant au caractère culturel du dispositif de la différence des sexes? Autant de questions qui peuvent être soulevées au moment d’interroger les textes, en recourant aux notions de détermination et d’indétermination, de brouillage et de glissement du genre, qui sont reliées de près à celle de l’identité sexuelle. Chaque texte littéraire recèle une vision du genre sexuel et constitue à ce titre un lieu de médiation où il est possible de reproduire ce dispositif ou de le subvertir. Aborder la question du genre vient ouvrir, en quelque sorte, celle du féminin et poser, à ses côtés, celle du masculin, et, plus globalement, celle de la division du monde.
https://www.editions-rm.ca/livres/lectures-du-genre/
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; genre; identité sexuelle; identités LGBTQIA2+; lit3495; premier cycle; queer; thématiques; écriture des femmes*; études littéraires

The art of history African American women artists engage the past - Collins, Lisa Gail (Rutgers University., 2002)
In this lively and engaging book, Lisa Gail Collins examines the work of contemporary African American women artists. Her study comes at a time when an unprecedented number of these artists-photographers, filmmakers, painters, installation and mixed-media artists-have garnered the attention and imagination of the art-viewing public. To better understand the significance of this particular historical moment in American visual arts, Collins focuses on four "problems" that recur when these artists confront their histories: the documentation of truth; the status of the black female body; the relationship between art and cultural contact and change; and the relationship between art and black girlhood. By examining the social and cultural histories which African American women artists engage, Collins illuminates a dialogue between past and present imagemakers. The Art of History is a major contribution to the study of American visual culture. It will be of use to both scholars and students in art history, African American studies, American studies, and women's studies.
Keywords: afro-féminisme; amériques; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; fem1000; femmes* afro-américaines; féminisme afroaméricain; féminismes noirs; pratiques féministes; premier cycle; régions géographiques; thématiques; états-unis

L'éternel féminin: une histoire du corps intime - Fontanel, Béatrice (Éditions du Seuil, 2001)
Un ouvrage fascinant, aux images voluptueuses, sur les étranges canons de la beauté féminine à travers les âges. Ainsi, on apprend que l'engouement pour le teint pâle a contraint les femmes à fuir le soleil et à appliquer sur leur visage des plâtres toxiques. De même, en épluchant les recettes de beauté du 15e et 17e siècles, l'auteure égrène l'extraordinaire variété des ingrédients pour les soins du visage : poudre de perles de corail, lard finement râpé, fiente de chat, poudre de cloportes, foie de thon pourri, oeufs de fourmi, etc. Les exemples cités peuvent susciter un certain dégoût, mais l'auteure rappelle que nos pratiques modernes ne sont pas sans contradictions : chirurgie esthétique (visages tirés, lèvres boursouflées, paupières allégées) sans oublier les coûts astronomiques des crèmes de beauté - que sait-on sur la fabrication de ces produits? [SDM].
Section: 142, [1] pages : illustrations en couleur ; 26 cm
Keywords: approches et analyses; arts; care; corps; cours; discipline; histoire et politique; lit4700; patriarcat; premier cycle; systèmes d'oppressions; thématiques; études littéraires

La mue de l'hermaphrodite: roman - Georges, Karoline (Leméac, 2001)
Premier roman de Karoline Georges et premier roman de la génération techno paru en 2001, La Mue de l’hermaphrodite porte un regard dérangeant sur le début du XXIe siècle et étonne par son actualité vingt ans plus tard. À travers le genre de la science-fiction, l’autrice explore avec acuité les enjeux éthiques liés aux identités de genre, au contrôle technocratique par la surveillance à outrance, à la consommation de drogues et au désir perpétuel de l’humain de fuir le réel. Emprisonné dans une cellule expérimentale sous l’oeil avide du cyberréseau, un être né hermaphrodite doit se confesser d’un crime. Face à ses détracteurs invisibles, l’hermaphrodite s’ausculte et se raconte tout en condamnant l’État qui l’a créé. Le roman suit cet être jusqu’au bout de sa marginalisation : de son enfance hypermédiatisée, à la déchéance de son corps, en passant par sa conquête d’un empire de psychotropes jusqu’à la mue terminale d’Hermany Mésange.
Section: 109 pages ; 22 cm
Keywords: 1900-1999; LGBTQIA2+; arts; corps; cours; discipline; identités LGBTQIA2+; lit4700; littérature; premier cycle; périodes historiques; roman; thématiques; études littéraires

Women artists: femmes artistes du XXe et du XXIe siècle - Grosenick, Uta; Fruhtrunk, Wolf (Taschen, 2001)
À l'appui de nombreuses illustrations et textes informatifs, ce livre se veut une introduction à la vie et à l'oeuvre de 46 femmes artistes contemporaines, qui ont marqué l'art du 20e siècle d'une empreinte durable, et qui influenceront encore l'art du 21e siècle. Tous les courants et tendances sont présentés : peinture, dessin, sculpture, photographie, cinéma, vidéo et Internet, installations, travail sur la nature ou le corps.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; arts; corps; cours; discipline; environnement; femmes* artistes; har4600; histoire de l'art; premier cycle; périodes historiques; thématiques

Journal de la création - Huston, Nancy (Actes sud, 2001)
Pendant des millénaires, tout paraissait simple : aux hommes la création, aux femmes la procréation ; aux hommes l'esprit et aux femmes le corps. L'émancipation féminine a bousculé cette distribution des rôles et mis à mal des métaphores séculaires : la muse féminine, l'œuvre d'art comme amante ou comme " enfant " de l'artiste. Mais trouver un nouveau modus vivendi n'est pas facile pour autant. Mettant à profit une certaine et curieuse forme de clairvoyance liée, dans son esprit, aux métamorphoses de son corps de femme enceinte, Nancy Huston s'est penchée sur les histoires souvent douloureuses de Sand et Musset, Virginia et Leonard Woolf, Scott et Zelda Fitzgerald, Sartre et Beauvoir. Le récit de ses recherches sur les couples d'écrivains et le journal de sa propre grossesse se croisent, se répondent et se complètent pour évoquer les mystères de l'amour, de l'inspiration, du couple et de la création.
Donné en lecture : 11-56
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; cours; création; discipline; europe; fem1000; littérature; premier cycle; procréation; périodes historiques; régions géographiques; santé; santé reproductive; thématiques; études littéraires

Corps, sexe et art: dimension symbolique - Pearl, Lydie (L'Harmattan, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques

Looking like what you are sexual style, race, and lesbian identity - Walker, Lisa (New York University Press, 2001)
Looks can be deceiving, and in a society where one's status and access to opportunity are largely attendant on physical appearance, the issue of how difference is constructed and interpreted, embraced or effaced, is of tremendous import. Lisa Walker examines this issue with a focus on the questions of what it means to look like a lesbian, and what it means to be a lesbian but not to look like one. She analyzes the historical production of the lesbian body as marked, and studies how lesbians have used the frequent analogy between racial difference and sexual orientation to craft, emphasize, or deny physical difference. In particular, she explores the implications of a predominantly visible model of sexual identity for the feminine lesbian, who is both marked and unmarked, desired and disavowed. Walker's textual analysis cuts across a variety of genres, including modernist fiction such as The Well of Loneliness and Wide Sargasso Sea, pulp fiction of the Harlem Renaissance, the 1950s and the 1960s, post-modern literature as Michelle Cliff's Abeng, and queer theory.
Keywords: arts; corps; discipline; identités LGBTQIA2+; littérature; personnes lesbiennes; thématiques; études littéraires

Gendered appetites: Feminisms, Dorothy Allison, and the body - Jarvis, Christina (Women's Studies, 2000)
Keywords: amériques; arts; corps; discipline; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis; études littéraires

Dorothy Allison : la peau porte-parole - Peterson, Michel (Nuit blanche, 2000)
Portrait et parcours de cette écrivaine américaine, à partir de son recueil de textes sur l'amour lesbien, intitulé «Peau».
Keywords: amériques; approches et analyses; arts; corps; discipline; lesbianisme; personnes lesbiennes; régions géographiques; thématiques; états-unis; études littéraires